Urban sustainable development: inner logic and exploration in Guangzhou - Luo, Xiuming; Yan, Zedong; Ma, Chong; Xie, Jinlong (Frontiers in Built Environment, 2024)
This study explores the influence on urban sustainable development performance of residents’ resettlement as a result of urban renewal activities, aiming to develop a system dynamics model to simulate the performance of urban sustainable development performance at the perspective of urban renewal. The system dynamics model consists of four subsystems, which are urban economic sector, social service sector, demolition and resettlement sector, and industrial development sector. It was used to simulate the sustainable development performance of Guangzhou city. In the seven scenarios simulated, it is found that increasing the ratio of in-site rehousing and off-site rehousing at the same time can help to promote the sustainable development of the city. The results show that the system dynamics model can effectively simulate the impacts of urban renewal on sustainable development performance, and provides a reference for decision makers to formulate urban sustainable development strategies.